Recovery from exercise - Leigh, Richard (Video Education Australasia [production company] Insight Media [distributor], 2005)
Shows how the three main energy systems of the body (the ATP-CP, lactic acid, and aerobic systems) carry out physical activity. Examines the effects of exercise on the human body and presents strategies and recovery techniques, including fluid and carbohydrate replenishment, active recovery, and stretching.